Paradoxical reduction of plasma lipids and atherosclerosis in mice with adenine-induced chronic kidney disease and hypercholesterolemia - Padalkar, Mugdha V.; Tsivitis, Alexandra H.; Gelfman, Ylona; Kasiyanyk, Mariya; Kaungumpillil, Neil; Ma, Danyang; Gao, Michael; Borges, Kelly A.; Dhaliwal, Puneet; Nasruddin, Saud; Saji, Sruthi; Gilani, Hina; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Atherosclerotic cardiovascular disease is prevalent among patients with chronic kidney disease (CKD). In this study, we initially aimed to test whether vascular calcification associated with CKD can worsen atherosclerosis. However, a paradoxical finding emerged from attempting to test this hypothesis in a mouse model of adenine-induced CKD. Methods We combined adenine-induced CKD and diet-induced atherosclerosis in mice with a mutation in the low-density lipoprotein receptor gene. In the first study, mice were co-treated with 0.2% adenine in a western diet for 8 weeks to induce CKD and atherosclerosis simultaneously. In the second study, mice were pre-treated with adenine in a regular diet for 8 weeks, followed by a western diet for another 8 weeks. Results Co-treatment with adenine and a western diet resulted in a reduction of plasma triglycerides and cholesterol, liver lipid contents, and atherosclerosis in co-treated mice when compared with the western-only group, despite a fully penetrant CKD phenotype developed in response to adenine. In the two-step model, renal tubulointerstitial damage and polyuria persisted after the discontinuation of adenine in the adenine-pre-treated mice. The mice, however, had similar plasma triglycerides, cholesterol, liver lipid contents, and aortic root atherosclerosis after being fed a western diet, irrespective of adenine pre-treatment. Unexpectedly, adenine pre-treated mice consumed twice the calories from the diet as those not pre-treated without showing an increase in body weight. Conclusion The adenine-induced CKD model does not recapitulate accelerated atherosclerosis, limiting its use in pre-clinical studies. The results indicate that excessive adenine intake impacts lipid metabolism.